Money, "laissez-faire" and the underground economy - Σολδάτος, Γεράσιμος; Ζήκος, Σπύρος (SPOUDAI Journal of Economics and Business, 2000)
The fact that the use of money enables underground transactions to be kept undetected by the authorities, implies that its variation changes this ability too, thus imposing transaction costs. Variations in money alter in addition the interest rate and hence, the opportunity cost of holding money, which is another money related factor affecting underground economy. The present paper argues that this double role of money makes it useful in controlling underground activities, more useful than a campaign against tax evasion, which constitutes a motive for going underground. The whole discussion evolves around this thesis, tackling it analytically from different points of view. JEL Classification: E49, E59, Η 26